Local and Regional Tectonic Influence of Territory on Geohazard of Dam of Radioactive Waste Tailings (Ukraine) - Orlinska, Olha; Орлінська, Ольга; Pikarenia, Dmytro; Пікареня, Дмитро Сергійович; Rudakov, Leonid; Рудаков, Дмитро Миколайович; Hapich, Hennadii; Гапіч, Геннадій Васильович (MDPI AG, 2026)
Uranium production tailing ponds in Kamyanske (Ukraine) are objects of increased radioecological danger. Violation of the stability and integrity of containment dams threatens the uncontrolled spread of radionuclides. The purpose of this study is to comprehensively assess the factors affecting the technical condition and environmental safety of the Sukhachivske tailing dam. The study included a visual inspection and detailed geophysical work using the natural pulse electromagnetic field of the Earth (NPEMFE) method. This method was chosen to identify hidden filtration paths and stress zones in the body of the earth dam. An analysis of the spatial distribution of waterlogging, filtration, and fissuring in the hydraulic structure was performed. Based on the results of the NPEMFE survey, six zones with varying degrees of waterlogging and stress–strain states of the structure were identified. The presence of externally unmanifested filtration paths and suffusion areas was established, and a tectonic scheme of fracture development in the dam body was compiled. A correlation was found between the dominant azimuths of crack extension (70–79° and 350–359°) and the directions of regional tectonic lineament zones, at the intersection of which the tailing pond is located. It has been established that modern tectonic movements along fault zones create zones of permeability, which serve as primary pathways for water filtration and further development of suffusion. This conclusion introduces a new tectonic feature for risk diagnosis and monitoring of similar hydraulic structures. Хвостосховища уранового виробництва в Кам'янському (Україна) є об'єктами підвищеної радіоекологічної небезпеки. Порушення стійкості та цілісності захисних дамб загрожує неконтрольованим поширенням радіонуклідів. Метою цього дослідження є комплексна оцінка факторів, що впливають на технічний стан та екологічну безпеку Сухачівського хвостосховища. Дослідження включало візуальний огляд та детальні геофізичні роботи з використанням методу природного імпульсного електромагнітного поля Землі (NPEMFE). Цей метод був обраний для виявлення прихованих шляхів фільтрації та зон напружень у тілі земляної дамби. Було проведено аналіз просторового розподілу заболочення, фільтрації та тріщинуватості в гідроспоруді. За результатами дослідження NPEMFE було виявлено шість зон з різним ступенем заболочення та напружено-деформованим станом споруди. Встановлено наявність зовні непроявлених шляхів фільтрації та ділянок суфозії, а також складено тектонічну схему розвитку тріщинуватості в тілі дамби. Було виявлено кореляцію між домінуючими азимутами поширення тріщин (70–79° та 350–359°) та напрямками регіональних тектонічних лінеаментних зон, на перетині яких розташоване хвостосховище. Встановлено, що сучасні тектонічні рухи вздовж зон розломів створюють зони проникності, які служать основними шляхами для фільтрації води та подальшого розвитку суфозії. Цей висновок вводить нову тектонічну ознаку для діагностики ризиків та моніторингу подібних гідротехнічних споруд.
Локальний та регіональний тектонічний вплив території на геонебезпеку дамби хвостосховища радіоактивних відходів (Україна)
Keywords: suffusion; суфузія; tailing storage facility; хвостосховище; radioactive waste; радіоактивні відходи; environmental safety; екологічна безпека; natural pulsed electromagnetic field of the Earth; природне імпульсне електромагнітне поле Землі; fracturing; тріщинуватість; tectonic feature; тектонічна особливість; filtration; фільтрація